Effect of Buzhong Yiqi decoction on anti-acetylcholine receptor antibody and clinical status in juvenile ocular myasthenia gravis. Issue 44 (5th November 2021) - Li, Jiaduo; Qi, Guoyan; Liu, Yaling
Abstract : Abstract: Ocular myasthenia gravis (MG) is the mainly widespread type of MG among juveniles. Buzhong Yiqi decoction (BZ) is a well-known traditional Chinese medicine prescription for treating MG. It has rarely been discussed whether the concentration of anti-acetylcholine receptor (AChR) antibodies is related to the clinical status of juvenile ocular myasthenia gravis (JOMG) treated with BZ. The patients with JOMG who had more than once AChR-antibody (ab) test and treated with BZ were retrospectively identified from June 2013 to January 2020 in the first hospital in Shijiazhuang. The presence or absence of ocular symptoms was used to grade the effectiveness of treatment. Generalized estimating equations logistic regression analysis was used to evaluate the effect of AChR ab concentration on the clinical status of MG. A total of 549 AChR-ab tests were performed in 135 patients, and the corresponding clinical status was recorded. One hundred two patients received treatment with BZ only and 33 combined with immunosuppressive drugs. In the group receiving only BZ treatment, the anti-acetylcholine receptor ab concentration was positively correlated with the clinical score after treatment. The results suggest that BZ could affect the AChR-ab. Repeated AChR-ab assays can provide information about the clinical status. For JOMG patients who only receive Buzhong Yiqi Decoction treatment, this can support treatment decisions.